Ekološka ozaveščenost osnovnošolcev v smislu varčevanja z energijo in ločevanjem odpadkov - Hribar, Simona (Revija za elementarno izobraževanje, 2011)
Ecological Awareness of Primary School Pupils in the Sense of Saving Energy and Sorting Waste. The article presents research we conducted to find out to what extent our pupils sort out garbage and to what extent they save energy at home and at school. We wanted to examine the environment they live in, whether they live in a block of flats or in a house or in a village or a city. Lastly, but not least, we were interested in how pupils regard their school’s participation in the ‘Eco-school as a way of life’ project. The research indicates that the pupils who live in the city are less aware of separating garbage as well as saving energy than the ones who live in villages. As for sorting garbage at home, we did not find any differences between the pupils from the city and the village. The largest amount of sorting was the separation of wastepaper, while sorting organic waste was done less. Glass, plastic or alkaline waste were separated the least. There were a high percentage of completed questionnaires that stated that the pupils do not sort out metal.
Keywords: ecology; energy saving; waste sorting